The Effects of an Instructional Model Integrating Total Physical Response Method and Code-Switching Technique on English Ability of Kindergarteners - Chiropasworrapong, Poonyawee; Hemchayart, Worawan; Traiwichitkhun, Duangkamol (Journal of Multidisciplinary in Social Sciences, 2023)
The research studied the effectiveness of an instructional model integrating total physical response (TPR) method and code-switching technique on English ability of kindergarteners, aged 5-6 years old, at public schools in the central region, Thailand, under the Department of Local Administration. The sample consisted of 38 kindergarteners in Thesaban 1 Baan-Sampran school (the experiment group) and Thesaban 1 Wat Teandud school (the control group) in Nakorn Pathom Province. Research instruments were the test of English ability of kindergarteners, and the self-report of the satisfaction of learning English in the experimental group. Arithmetic means, standard deviation, and t-test were applied to analyze the results of the study. The research found that after the experiment, the score on English ability of the experiment group were higher than the control group with statistically significant differences at .01 level and the average satisfaction of learning English was 94.74%